SITUASI DAN KONDISI PERLAWANAN TERHADAP PENJAJAHAN BELANDA DI INDONESIA - Eka Damayanti Hasibuan; Muhammad Basri; Diana Siregar (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Resistance is defined as the struggle of the Indonesian people to free themselves from oppressive circumstances or movements either without or with armed violence. This arbitrary action and oppression caused a strong reaction from Indonesian society. In facing Dutch colonialism, Indonesian society experienced various changes and negative influences on people's lives. This research is a type of literature study research with research methods that examine ideas, knowledge or findings obtained through literature, formulating theoretical and methodological contributions to certain topics. . The results of this research found that in the face of Dutch colonialism, Indonesian society experienced various changes and negative influences on people's lives. This includes changes in the economy, education, religion and work systems which cause suffering for the Indonesian people. As a result, some resistance was carried out physically or armed, especially using traditional weapons such as keris, spears, machetes, swords and bamboo tubes. including the Padri War and Saparua War, and the Palembang